Transformation of The TNI's Military Strategy in Facing Modern Conflicts with The Adaptive Model of Military Strategy in Navigating Technological Challenges and Geopolitical Shifts Effectively - Arip Supriyadi; Budi Setyoko (Transpublika Publisher, 2025)
The transformation of military strategy in dealing with modern conflicts has become crucial amidst rapidly changing geopolitical dynamics and technological advances. This research aims to develop the Adaptive Model of Military Strategy to Overcome Technological Threats and Geopolitical Changes as the Transformation Of The TNI's Military Strategy in Facing Modern Conflicts. This research used descriptive qualitative research, with a literature review and interviews with the informants. The research locations include strategic institutions such as the Indonesian Ministry of Defense, the TNI Headquarters, and defense policy research institutes. The time of the research started from March to May 2025. This research found that the Adaptive Model of Military Strategy to Overcome Technological Threats and Geopolitical Changes can anticipate unexpected, uncertain, and ambiguous conditions in facing the modern conflict. On the other hand, this model can assist in the Design and Implementation of Defense Strategy Policies. This model has six pillars: Integration of Defense Technology and Artificial Intelligence, Adaptive Risk Management in Command and Control Systems, Multi-Domain Collaboration and Defense Diplomacy, VUCA-Responsive Based National Resilience, Assessment and Mapping of Global and Regional Geopolitical Dynamics, and identifying asymmetric Strategic Risks. Moreover, the conclusion of this research is the transformation of the TNI's military strategy in response to modern conflicts can be achieved through the implementation of the Adaptive Model of Military Strategy to Overcome Technological Threats and Geopolitical Changes.